Participation In An Online Forum: A Case Study Of UTM Students - Wan Mansor , Wan Fara Adlina; Bala, Shalini Srika (2010)
Virtual world or environment such as Online Forum is one of the predominantly text-base asynchronous Computer Mediated Communication (CMC) tools. Since early 1990s, Online Forum has generated much interest among second language researchers. However, to date, not many studies have focused on Online Forum as a platform for language learning. For the purpose of this study, in UTM, a fully-fledged virtual forum called MyLine, was chosen and analyzed to benefit students in their language learning and communication skills. This study began investigating on the nature of interaction among students in online forum, the factors that influences students’ participation and language use within the electronic medium and finally on the reasons for their participation. Data were gathered through online observation and questionnaire. Content analysis was also done on the messages posted. Through the data collection, it was found that there are some patterns of interaction between the students. Besides that, there are a few factors that influenced students’ participation such as accessibility of Internet, speed of access and their computer skills. There are a few patterns of language used in online forum which influence the students’ language use. In particular, most of the students participated in online forum because i) the topics discussed are interesting, ii) coursework mark given by lecturer and iii) online forum motivate them to communicate by improving their language. Thus, MyLine forum is an affective medium to provide equal opportunity to second language learners with different levels of proficiency to participate without hesitant.